Numerical models for ground deformation and gravity changes during volcanic unrest: simulating the hydrothermal system dynamics of a restless caldera - A. Coco (Solid Earth, 2016)
Ground deformation and gravity changes in restless calderas during periods of unrest can signal an impending eruption and thus must be correctly interpreted for hazard evaluation. It is critical to differentiate variation of geophysical observables related to volume and pressure changes induced by magma migration from shallow hydrothermal activity associated with hot fluids of magmatic origin rising from depth. In this paper we present a numerical model to evaluate the thermo-poroelastic response of the hydrothermal system in a caldera setting by simulating pore pressure and thermal expansion associated with deep injection of hot fluids (water and carbon dioxide). Hydrothermal fluid circulation is simulated using TOUGH2, a multicomponent multiphase simulator of fluid flows in porous media. Changes in pore pressure and temperature are then evaluated and fed into a thermo-poroelastic model (one-way coupling), which is based on a finite-difference numerical method designed for axi-symmetric problems in unbounded domains. Informed by constraints available for the Campi Flegrei caldera (Italy), a series of simulations assess the influence of fluid injection rates and mechanical properties on the hydrothermal system, uplift and gravity. Heterogeneities in hydrological and mechanical properties associated with the presence of ring faults are a key determinant of the fluid flow pattern and consequently the geophysical observables. Peaks (in absolute value) of uplift and gravity change profiles computed at the ground surface are located close to injection points (namely at the centre of the model and fault areas). Temporal evolution of the ground deformation indicates that the contribution of thermal effects to the total uplift is almost negligible with respect to the pore pressure contribution during the first years of the unrest, but increases in time and becomes dominant after a long period of the simulation. After a transient increase over the first years of unrest, gravity changes become negative and decrease monotonically towards a steady-state value. Since the physics of the investigated hydrothermal system is similar to any fluid-filled reservoir, such as oil fields or CO2 reservoirs produced by sequestration, the generic formulation of the model will allow it to be employed in monitoring and interpretation of deformation and gravity data associated with other geophysical hazards that pose a risk to human activity.